Impact of exchange rate regime in the economy of the Colombian flower industry (2013)
One of the strongest sectors in the economy of our country is the floriculturist sector, which stands out as one of the most determinant performer in the negotiations of the FTA ́s (Free Trade Agreements); which is currently running in our country. Besides this sector, the floriculturist sector is a first order protagonist for the local and world economy, in the domestic market, this is agricultural activity that generates more jobs per unit area, with an employment average of 16 peoples per hectare of crop. This sector has several natural and economic advantages, which increases the competitive production itself in front of the export flower ́s market. Some of the geographic advantages are: topical location, different microclimates due to the topography and optimal conditions of light, moist, temperature and fertility in our country. Those factors stimulate the best quality of our flower ́s production to in order to be able to compete worldwide. The productive sector of our country is affected by the constant fluctuations in the exchange rate of our currency. On the one hand, these changes show a major impact of profitability in our flower industry. On the other hand, the influence of the exchange rate between the currencies: dollar and pesos. At this moment, we find the main effects for this sector, which impact primarily in two ways. The internal area generated by payments on our currency on concepts of labor, transport services and domestic and external one, the payments generated by the purchase of imported inputs such as fertilizers and meshes for the care of the flowers. Currently, Colombia has many FTAs contracts signed with several world power countries, which benefit our overall flower industry and reducing taxes for our country. One of the most important agreements signed is the one made with United States, which is our largest flowers buyer and which is also the country that absorbs almost 85% of total export amounts.